Desain Simulasi Interface Pistol G2 COMBAT Kal. 9 mm dengan Simulator Pimp My Gun - Praditasari, Wibby Aldryani Astuti; Ariateja, Dananjaya; Fatmawati, Uvi Desi; Hutapea, Herwin Melyanus; Tjahjadi, Tjahjadi; Sunardi, Agus; David, Muhammad; Friskilla , Angelita; Dewanata, Pandhu (Pusat Teknologi Instrumentasi dan Otomasi (PTIO) - Institut Teknologi Bandung, 2023)
The development of firearms has been included as an introduction and use at the University of Defense. However, using firearms that are not used freely is a barrier for students to understand the ins and outs of firearms better. Therefore, in this research, firearms are replaced with interface simulation design. One firearm that needs to be designed for interface simulation is the G2 Combat pistol. The reason for using the G2 Combat pistol in making an interface simulation design is because the Indonesian armed forces have widely used it. The interface simulation design uses Pimp My Gun software. The method of designing the G2 Combat pistol interface simulation uses the waterfall method. The waterfall method is considered easy and systematic. After the interface simulation design is carried out, the results are compared with the original item or image, photo, and others. Assessment of the G2 Combat pistol interface simulation design with the original pistol by comparing and finding the level of similarity. The assessment results are 87.61% at imgonline.com and 86.14% at blue2digital.com. With two assessment results close to 100%, the G2 Combat pistol interface simulation design is successful. However, there still needs to be improvements so that the interface simulation design is even better in the future.